Lean Women on Metformin and Oral Contraceptives for Polycystic Ovary Syndrome Demonstrate a Dehydrated Osteosarcopenic Phenotype: A Pilot Study - Stefanaki, Charikleia (Nutrients, 2019)
Scarce data exist on the body composition of lean women with polycystic ovary syndrome (PCOS) on treatment with metformin and oral contraceptives (OCs). Thirty-four lean (body mass index 18.5–24.9 kg/m(2)) women (17 with PCOS on metformin and OCs treatment for six months and 17 controls) aged 18–40 years were assessed for body composition parameters (fat, muscle, glycogen, protein masses, bone masses, and body water compartments) and phase angles. PCOS patients demonstrated lower muscle, glycogen and protein masses (U = 60, p = 0.003), along with a lower bone mineral content and mass (U = 78, p = 0.021; U = 74, p = 0.014) than their healthy counterparts, while total and abdominal fat masses were similar between the two groups. PCOS patients also exhibited increased extracellular body water (U = 10, p < 0.001) and decreased intracellular water, compatible with low-grade inflammation and cellular dehydration. Key differences in body composition between women with PCOS and controls demonstrated an osteosarcopenic body composition phenotype in PCOS patients. A confirmation of these findings in larger studies may render osteosarcopenia management a targeted adjunct therapy in women with PCOS.